Finding Bronies – The accidental audience of My Little Pony: Friendship is Magic - Burdfield, Claire (Journal of Popular Television, The, 2015)
Abstract The practice of audience segregation, demographic profiling and manufactured viewerships has become common practice in the television industry since the turn towards niche programming and narrowcasting in an increasingly multichannel environment. While much critical scholarship has been devoted to the way that media companies undertake extensive market research to target their products to specific demographic segments, this article concentrates on the way that untargeted and unexpected viewers have coalesced around certain television programmes, and become the ‘accidental audience’. ‘Bronies’ have become the most well-known accidental audience in recent years, and are a perfect case study by which this phenomenon can be examined. The article therefore explores the way that accidental audiences develop, and how they offer both opportunity and threat to the managed selling of media brands. This article will also engage with the issues surrounding identifying and responding to these accidental audiences. Using the ‘Brony’ fandom of My Little Pony: Friendship is Magic, this article asks how accidental audiences develop and how, in particular, the Internet serves to shape and cultivate them.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qcHR2LjMuMS4xMjdfMQ